Preliminary efficacy and safety analysis: 12-month results in 83 patients using a novel approach of widefield radiation therapy for extensive skin field cancerization with or without keratinocyte cancers. (4th July 2022) - Potter, Andrew E.; Baker, Christopher; Shumack, Stephen; Sinclair, Robert; Curran, Walter J.; Christie, David; Wong, Bradley; Foley, Peter; O'Brien, Peter; Spelman, Lynda; ,
Abstract: Purpose: Evaluate the use of widefield radiation therapy (RT) in the management of extensive skin field cancerization (ESFC) with/without keratinocyte cancer (KC). Methods: The National Dermatology Radiation Oncology Registry is a multidisciplinary collaboration (dermatologists and radiation oncologists). It captures disease description, prior therapies, radiation prescription, clinical effect, skin cosmesis scores, and toxicity data. This analysis included 12-month follow-up data on 89 treated fields from a subset of 83 patients. Results: Clinical success (>90% field clearance) was 96% (ESFC, n = 63) and 88% (ESFC with KC, n = 26). Complete lesion response was seen in 96% of evaluable ( n = 25) ESFC with KC. Recurrence (4/89 [5%]) and appearance of new lesions (10/89 [11%]) were minimal. Cosmetic outcome was excellent/good in 98% ESFC and 96% ESFC with KC. Grade 1–2 acute radiation dermatitis occurred in up to 80% of treated fields. The frequency of Grade 3 acute skin toxicities was low. Conclusions: Registry data demonstrate the potential for widefield RT to treat patients with significant skin pathology who have exhausted other therapies and require durable, minimally invasive treatment options. At 12 months, observed clinical success rates were higher than those reported for topical interventions for ESFC. Ongoing follow-up is required to determine longer term outcomes.